calculus

posted by .

Express as a single logarithm

ln(a)+1/2ln(b)

2ln4-ln2

  • calculus -

    ln a + (1/2) ln b
    = lan a + ln )b^(1/2))
    = ln (a√b)

    you try the second, and let me know what you got

  • calculus -

    2ln4-ln2
    =ln(16)-ln2
    =ln(16/2)
    =ln8?

  • calculus -

    correct

  • calculus -

    Thank you =)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. algebra 3-4

    im in a cal class but were reviewing algebra stuff now. and i have 1 more questions. it says. express the given quantity as a single loragithms 2ln4-ln2 so is it 2ln(2) please tell me if im getting the right answers and if im not then …
  2. Calculus

    Write the logarithm of a single quantity: 2ln(x)+ln(4)-(1/2)ln(9)
  3. calculus

    Express as a single logarithm ln(a)+1/2ln(b) 2ln4-ln2
  4. Algebra

    Express as a single Logarithm and Simplify: 2/3ln(x^2+1)+1/2ln(x^2-1)-1/2ln(x+1)
  5. Algebra II

    Did I do this correctly? Use log laws to write the following expression as a single logarithm. 3/2 ln25 + 3 ln2 = ln25 3/2 + ln2^3 = ln125 + ln2^3 =ln125 + ln8 =ln(125*8) =ln1000
  6. Algebra II-Please check

    Did I do this correctly? Use log laws to write the following expression as a single logarithm. 3/2 ln25 + 3 ln2 = ln25 3/2 + ln2^3 = ln125 + ln2^3 =ln125 + ln8 =ln(125*8) =ln1000
  7. ALGEBRA

    Contract the expressions. That is, use the properties of logarithms to write each expression as a single logarithm with a coefficient of 1. text ((a) ) ln\(3\)-2ln\(4\)+ln\(8\) ((b) ln\(3\)-2ln\(4+8\) (c) )ln\(3\)-2(ln\(4\)+ln\(8\))
  8. ALGEBRA

    Contract the expressions. That is, use the properties of logarithms to write each expression as a single logarithm with a coefficient of 1. text((a) ) ln\(3\)-2ln\(4\)+ln\(8\) text((b) )ln\(3\)-2ln\(4+8\) text((c) )ln\(3\)-2(ln\(4\)+ln\(8\))
  9. Calculus

    Write as a single logarithm of a single quantity ln(3)+1/2ln(x+2)-4ln(1+sqrtx)
  10. PreCalculus - Need help, due tonight

    1. Rewrite the expression 1/2ln(x – 6) + 3ln(x +1) as a single logarithm. 2. Rewrite the expression 1/3[ln x – 2ln(1 – x)] as a single logarithm.

More Similar Questions